A Biomedical Informatics Perspective on Human Factors: - Meyer, R.; Section Editor for the IMIA Yearbook Section on Human Factors (Yearbook of Medical Informatics, 2012)
to select and summarize excellent research published during 2011 in the study of human factors in bio-medical informatics.we attempt to derive a synthetic overview of the activity and new trends in this field, from a wide selection of worldwide research papers published during 2011.We selected four papers. The first one presents an international effort aiming to design a guideline for good evaluation practice in health informatics (GEP-HI) [2]. The second reviews medical errors taxonomies from a human factor perspective [3]. The third one advocates the need to systematically perform a deep evaluation process after all healthcare information technologies project deployment [4]. The fourth one explores exit strategies performed by clinician using health record system and how/why we need to anticipate them [5].This papers selection will provide our readers with valuable evidences on past and existing research in the specific field of human factors in healthcare informatics. It can also act as a foundation for stakeholders in the healthcare industry that emphasize the significance of human factors and ergonomics in designing healthcare information systems of the future.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; human factors